The Effect Of Multiple To Box Jump Training On Shooting Skills In Football Game In Senior High School Negeri 7 Bengkulu Selatan - Aprido, Ikat; Martiani, Martiani; Ferdima, Feby Elra (Utami Publisher, 2025)
This study aims to the effect of multiple to box jump training on shooting skills in football games at SMA Negeri 7 Bengkulu Selatan. This type of research is quantitative research. The research sample totalled 20 people. The instrument used in this study was a test of leg muscle explosive power using box jump training. The results of the pretest shotting and posstest shotting tests carried out using multiple to box jump exercises obtained rtabel of 0.443 because the correlation coefficient between rxy = 0.93> 0.443 and an influence of 86.20% which means that with the discovery of a significant effect of multiple to box jump training on shooting skills in football games at SMA Negeri 7 Bengkulu Selatan, then multiple to box jump training on shooting skills in football games at SMA Negeri 7 Bengkulu Selatan.